The Effectiveness of Differentiated Learning Strategies on Elementary Students' Mathematical Critical Thinking Ability - Lisnawati, Lilis; Nirmala, Sri Dewi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the effectiveness of differentiated learning strategies in improving elementary students' mathematical critical thinking skills. The independent variable is the application of differentiated learning strategies, while the dependent variable is the students' mathematical critical thinking ability. A quantitative approach was used, utilizing a quasi-experimental design with a non-equivalent control group. The sample included 30 fourth-grade students from Al-Falaah Islamic Elementary School and 30 from Jombang 01 Ciputat Elementary School, selected through purposive sampling. Data collection involved tests, questionnaires, observation sheets, and interview guides, and the analysis was conducted using independent sample t-tests and N-Gain tests with the help of SPSS IBM 22.0 software. The statistical analysis showed a significant effect of differentiated learning strategies on critical thinking skills, with a p-value of 0.000 and an N-Gain score of 74.56%. This indicates a notable improvement in students’ abilities in interpretation, analysis, evaluation, and inference. Differentiated learning strategies accounted for 58% of the variation in outcomes, with the remaining 42% influenced by other factors. In conclusion, differentiated learning strategies significantly enhance elementary students' mathematical critical thinking, and educators are encouraged to adopt these methods to foster deeper cognitive engagement.